UJI KEAMANAN PRODUK TERHADAP KULIT DAN TINGKAT KESUKAAN REMAJA TERHADAP PRODUK KOSMETIK GEL PEMBERSIH WAJAH - Sitorus, Elly Nurita; Thaib, Cut Masyithah; Sofwan, Ahmad Gazali (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Cosmetics are used on the external parts of the human body (epidermis, hair, nails, lips, and external genital organs) or on the teeth and oral mucosa mainly to clean, perfume, change appearance and/or improve body odor or protect and maintain the body in good condition. There are many types of fake cosmetics on the market today, there are cosmetics that are circulating in the market illegally (not having a BPOM permit) which are dangerous for users. This study aims to determine the level of preference for the use of several facial cleansing gel cosmetic products and to determine the effect of different active ingredients on the level of preference of several facial cleansing gel products. The sample used in this study were 30 female adolescents aged 15-23 years. The research method used in this research is descriptive method with data collection techniques in the form of questionnaires and observations. The results showed that all facial cleansing gel cosmetic products used in this study had passed the BPOM notification and did not experience irritation on the respondent's skin when the irritation test was carried out for 2 x 24 hours. At the level of preference for cosmetic products seen from the overall product parameters, the respondents most preferred were Brand A Products, which were 362, then Brand B Products were 356, then Brand C Products were 320.